Understanding the use and usability of research evaluation studies, - Milzow, Katrin; Reinhardt, Anke; Söderberg, Sten; Zinöcker, Klaus (Research Evaluation, 2019)
Abstract. Many research funding and research performing organizations evaluate their operations or are subject to evaluations. A Working Group within Science E